A Potential Role for Felbamate in TSC- and NF1-Related Epilepsy: A Case Report and Review of the Literature. (22nd October 2015) - Mishal, Natanya M.; Arkilo, Dimitrios; Tang, Ju; Crawford, John R.; Wang, Sonya G.
Abstract : A 15-year-old girl with maternal inheritance of neurofibromatosis type 1 (NF1) and paternal inheritance of tuberous sclerosis complex (TSC) developed intractable epilepsy at age 5. Her seizures were refractory to adequate doses of four antiepileptic medications until felbamate was initiated at age 7. She has since remained seizure-free on felbamate monotherapy. Although felbamate has multiple mechanisms of action, it is thought to have its most potent antiepileptic effects through inhibition of the N -methyl-D-aspartate receptor (NMDAR). Previous studies have shown that the NMDAR is altered in varying epilepsy syndromes and notably in the cortical tubers found in TSC. The aim of this paper is to examine how felbamate monotherapy was able to achieve such robust antiepileptic effects in a unique patient and possibly offer a novel therapeutic approach to patients suffering from TSC- and NF-related epilepsy.